PERTUMBUHAN BEBERAPA JENIS LEGUMINOSA PAKAN YANG DITANAM PADA MEDIA TANAH BEKAS PENAMBANGAN BATUBARA DENGAN PERBAIKAN BAHAN ORGANIK - N. Ardhiansyah; Sumarsono Sumarsono; E.D. Purbajanti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
Conditions of post coal mining areal which having losing of vegetation because of coal exploration usually have high soils acidity (pH < 5) and poor of organic matter and nutrient for plants to growing good. The mining company usually adding organic matter and planting forage legume to increase the organic matter of the soils. Objective of the research was to evaluate the growth of some forage legume that adapted on post coal mining soils dan the respone of organic matter added for post coal mining soils. Factorial Completely Randomized Design (CRD) with three replications were used in this experiment. The first factor was four kinds of forage legume, i.e. (L1 = Centrosema pubescens; L2 = Pueraria javanica; L3 = Calopogonium mucunoides; and L4 = Crotalaria juncea). The second factor was three kinds of plant medium (M0 = non post mining soil; M1 = post coal mining soil without organic matter added; and M2 = post coal mining soil with organic matter added (2% of organic carbon)). Collected data were analyzed by Analysis of Variance (ANOVA), followed by Least Significant Defference (LSD) at 5% level of sifnificant. The result of this experiment showed that application of organic matter on post coal mining soils increased the measured parameters (plant height, root lenght, leaf number, and root nodule number) of forage legume. According to the result of this experiment, concluded that Calopogonium mucunoides (L3) was more adapted on post coal mining soils than the other forage legumes, but Crotalaria juncea (L4) was more responsive for organic matter added.